Sny Jarosława Iwaszkiewicza - subiectum w obiektywie - Igielska, Anna (Wydawnictwo Naukowe UAM, 2007)
Jarosław Iwaszkiewicz's Sny (Dreams) are interpreted by me in the context of Schopenhauer's philosophy of music and phenomenology of perception of Maurice Merleau-Ponty and a new phenomenology of Hermann Schmitz. The memory of Richard Wagner's Die Traume is treated by me not only as a point of reference for the description of the events of youth, but also as a form of presentation of the world of the presented story.
"Dreams" by Jarosław Iwaszkiewicz. The unself-ish self